Diaphragm pacing decreases hospital charges for patients with acute cervical spinal cord injury. Issue 1 (21st December 2020) - Kerwin, Andrew J; Diaz Zuniga, Yohan; Yorkgitis, Brian K; Mull, Jennifer; Hsu, Albert T; Madbak, Firas G; Ebler, David J; Skarupa, David J; Shiber, Joseph; Crandall, Marie L
Abstract : Background: Cervical spinal cord injury (CSCI) is devastating and costly. Previous research has demonstrated that diaphragm pacing (DPS) is safe and improves respiratory mechanics. This may decrease hospital stays, vent days, and costs. We hypothesized DPS implantation would facilitate liberation from ventilation and would impact hospital charges. Methods: We performed a retrospective review of patients with acute CSCI between January 2005 and May 2017. Routine demographics were collected. Patients underwent propensity matching based on age, injury severity score, ventilator days, hospital length of stay, and need for tracheostomy. We then adjusted total hospital charges by year using US Bureau of Labor Statistics annual adjusted Medical Care Prices. Bivariate and multivariate linear regression statistics were performed using STATA V.15. Results: Between July 2011 and May 2017, all patients with acute CSCI were evaluated for DPS implantation. 40 patients who had laparoscopic DPS implantation (DPS) were matched to 61 who did not (NO DPS). Following DPS implantation, there was a statistically significant increase in spontaneous Vt compared with NO DPS (+88 mL vs −13 mL; 95% CI 46 to 131 vs −78 to 51 mL, respectively; p=0.004). Median time to liberation after DPS was significantly shorter (10 vs 29 days; 95% CI 6.5 to 13.6 vs 23.1 to 35.3 days; p<0.001). Adjusted hospital charges were significantly lower for DPS on multivariate linear regression models controlling for year of injury, sex, race, injury severity, and age (p=0.003). Discussion: DPS implantation in patients with acute CSCI produces significant improvements in spontaneous Vt and reduces time to liberation, which translated into reduced hospital charges on a risk-adjusted, inflation-adjusted model. DPS implantation for patients with acute CSCI should be considered. Level of evidence: Level III.